PERAN KELOMPOK SADAR WISATA (POKDARWIS) DALAM MENINGKATKAN DAYA TARIK WISATA TEBING NANGGERANG DI DESA BAGOLO KECAMATAN KALIPUCANG KABUPATEN PANGANDARAN - Astriyani, Sari; Kiki Endah; Aditiyawarman, Aditiyawarman (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2025)
This study aims to determine the optimization of the role of the Tourism Awareness Group in increasing the tourist attraction of Nanggerang Cliff in Bagolo Village, Kalipucang District, Pangandaran Regency. Bagolo Village is the village that has the most tourism potential compared to other villages in Kalipucang District. One of them is the Nanggerang Cliff Tourist Attraction located in Bagolokolot Hamlet. However, the role of Pokdarwis in increasing the tourist attraction of Nanggerang Cliff cannot be said to be optimal, this is evidenced by the existence of problem indicators including 1) lack of adequate human resources in the Bagolo Village Pokdarwis both in managing and increasing the tourist attractions of Nanggerang Cliff. 2) The Bagolo Village Pokdarwis are not optimal in establishing cooperation with the government or the private sector in obtaining financial support for the development of Nanggerang Cliff. 3) lack of promotion carried out by the Bagolo Village Pokdarwis to introduce Nanggerang Cliff. The research method used is a qualitative research method with descriptive analysis. Based on the results of the study, it can be concluded that the role of Pokdarwis in increasing the tourist attraction of Nanggerang Cliff has not gone well.